Caffeine May Reduce Perceived Sweet Taste in Humans, Supporting Evidence That Adenosine Receptors Modulate Taste. Issue 9 (23rd August 2017) - Choo, Ezen; Picket, Benjamin; Dando, Robin
Abstract: Multiple recent reports have detailed the presence of adenosine receptors in sweet sensitive taste cells of mice. These receptors are activated by endogenous adenosine in the plasma to enhance sweet signals within the taste bud, before reporting to the primary afferent. As we commonly consume caffeine, a powerful antagonist for such receptors, in our daily lives, an intriguing question we sought to answer was whether the caffeine we habitually consume in coffee can inhibit the perception of sweet taste in humans. 107 panelists were randomly assigned to 2 groups, sampling decaffeinated coffee supplemented with either 200 mg of caffeine, about the level found in a strong cup of coffee, or an equally bitter concentration of quinine. Participants subsequently performed sensory testing, with the session repeated in the alternative condition in a second session on a separate day. Panelists rated both the sweetened coffee itself and subsequent sucrose solutions as less sweet in the caffeine condition, despite the treatment having no effect on bitter, sour, salty, or umami perception. Panelists were also unable to discern whether they had consumed the caffeinated or noncaffeinated coffee, with ratings of alertness increased equally, but no significant improvement in reaction times, highlighting coffee's powerful placebo effect. This work validates earlier observations in rodents in a human population.